HUBUNGAN PENYAKIT KOMORBID DIABETES MELITUS DENGAN LAMA RAWAT INAP PADA PASIEN COVID-19 DI RSUD DR. H. ABDUL MOELOEK BANDAR LAMPUNG - Fauzia, Nikma Syalsabiela; Kurniati, Intan; Sari, Ratna Dewi Puspita (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
ABSTRACT Background: Coronavirus disease-19 (COVID-19) is a type of acute respiratory disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). One of the main comorbid diseases of COVID-19 is diabetes mellitus (DM), where Indonesia is ranked 7th as the country with the highest number of people with DM in the world. The increase in the degree of morbidity and mortality due to comorbid diseases is related to the length of stay for COVID-19 patients in the hospital. The purpose of this study was to determine the relationship between comorbid DM and length of stay in COVID-19 patients who were hospitalized at RSUD Dr. H. Abdul Moeloek Bandar Lampung. Method: This research is an observational analytic study, with a cross sectional research design. The number of samples was 88 COVID-19 patients with and without comorbid DM taken from January-July 2021 in the medical record room of RSUD Dr. H. Abdul Moeloek Bandar Lampung. Samples were taken using simple random sampling technique, then the data were analyzed by univariate and bivariate analysis by Mann-Whitney Test. Results: Based on the Mann-Whitney statistical test, the p value for comorbid DM and length of stay in COVID-19 patients was 0.000 (p<0.05), meaning that there was a significant relationship between comorbid DM and length of stay in COVID-19 patients. Discussion: COVID-19 patients with comorbid DM are associated with a more severe condition of COVID-19 because it is associated with obesity, insulin resistance and low-grade inflammation which causes dysregulation of the body's immune system, thereby increasing the risk of developing ARDS and kidney injury which can be prolonged. inpatient. Conclusion: There is a statistically significant relationship between comorbid DM and length of stay in COVID-19 patients at Dr. Hospital. H. Abdul Moeloek Bandar Lampung.